Vertical distribution and migration of fish larvae in the NW Iberian upwelling system during the winter mixing period: implications for cross‐shelf distribution. (May 2015) - Rodriguez, J.M.; Cabrero, A.; Gago, J.; Guevara‐Fletcher, C.; Herrero, M.; Hernandez de Rojas, A.; Garcia, A.; Laiz‐Carrion, R.; Vergara, A.R.; Alvarez, P.; Piñeiro, C.; Saborido‐Rey, F.
Abstract: The vertical distribution and vertical migrations of fish larvae and implications for their cross‐shelf distribution were investigated in the northern limit of the NE Atlantic upwelling region during the late winter mixing period of 2012. The average positive values of the upwelling index for February and March of this year were far from normal, although the average hydrographic conditions during the period of study were of downwelling and the water column was completely mixed. Fish larvae, most in the preflexion stage, were concentrated in the upper layers of the water column and their distribution was depth stratified, both day and night. However, the larval fish community was not structured in the vertical plane and fish larvae did not show significant diel vertical migration (DVM), although five species showed ontogenetic vertical migration. In regions of coastal upwelling and in the absence of DVM, the location of fish larvae in the water column is crucial for their cross‐shelf distribution. Thus, the cross‐shelf distribution of the six most abundant species collected in this study can be explained by the surface onshore flow associated with coastal downwelling, retaining larvae of the coastal spawning species with a relatively shallow distribution in the shelf region and transporting larvae of slope spawning species onto the shelf. The wide vertical distribution shown by larvae of the offshore spawning species could be an adaptation of these species to ensure that some larvae reach the inshore nursery areas.